Model Pengembangan Kurikulum Pendidikan Islam dalam Lembaga Formal dan Nonformal - Shodiqin (Journal of Cultural Relativism (JCR), 2025)
The development of an Islamic education curriculum is a strategic step in facing the challenges of the times and the needs of students in various types of educational institutions. This study aims to describe the model of Islamic education curriculum development in formal and non-formal educational institutions, such as public schools, madrasas, and Islamic boarding schools. The method used in this study is library research with qualitative-descriptive data analysis. The results of the study indicate that each type of institution has its own unique curriculum development characteristics, ranging from a dichotomous model, an integrative mechanism, to an organism model that emphasizes the relationship between spiritual, social, and intellectual aspects. The conclusion of this article emphasizes the importance of relevance, flexibility, and integration of Islamic values in every aspect of the educational curriculum.